1993
DOI: 10.1002/ijc.2910540510
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine cells in colorectal adenocarcinomas: Incidence, hormone profile and prognostic relevance

Abstract: The occurrence of endocrine cells in 350 cases of colorectal adenocarcinoma was studied by immunohistochemistry for chromogranin A (CGA). The hormone profile of endocrine tumor cells, the correlation between endocrine differentiation and presence of other colorectal epithelial-cell lineages and the prognostic relevance of endocrine differentiation in colorectal cancer were investigated. CGA-positive tumor cells were found in 30% of cases, 21% showing moderate positivity and 9.0% extensive positivity. Of CGA-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
48
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 20 publications
5
48
1
Order By: Relevance
“…In the present series, cases having a neuroendocrine differentiated component in the primary tumors had a slightly shorter survival both from the time of diagnosis and the time from metastatic spread but statistical significance was reached for the latter case only, possible due to the relatively small sample size. Other literature data are in line with this observation [13,19,20], although some authors found no prognostic differences between neuroendocrine differentiated and conventional colorectal carcinoma [21]. No correlation was also observed with any clinical pathological parameter.…”
Section: Discussionsupporting
confidence: 80%
“…In the present series, cases having a neuroendocrine differentiated component in the primary tumors had a slightly shorter survival both from the time of diagnosis and the time from metastatic spread but statistical significance was reached for the latter case only, possible due to the relatively small sample size. Other literature data are in line with this observation [13,19,20], although some authors found no prognostic differences between neuroendocrine differentiated and conventional colorectal carcinoma [21]. No correlation was also observed with any clinical pathological parameter.…”
Section: Discussionsupporting
confidence: 80%
“…4 In addition, tumor histology can be an important prognostic indicator. In CRC, studies suggest that both signet ring cell and small cell tumors are associated with an adverse prognosis, [5][6][7] whereas other histologic types may carry a more favorable prognosis. 8 The prognosis of CRC mucinous tumors is more controversial, and some studies have reported a worse outcome for these tumors.…”
mentioning
confidence: 99%
“…Probably the most common pattern of neuroendocrine differentiation in GI neoplasms, however, is the presence of scattered tumor cells showing neuroendocrine differentiation in an otherwise typical adenocarcinoma. The presence of neuroendocrine cells in colonic adenocarcinomas (1)(2)(3)(4)(5) and gastric adenocarcinomas (6) has long been recognized. Although up to 42% of typical colon adenocarcinomas contain scattered chromogranin (CG)-positive cells (4), this finding does not seem to influence prognosis, and these tumors are not classified as mixed adenocarcinoma/ neuroendocrine tumors.…”
mentioning
confidence: 99%